PENINGKATAN KEMAMPUAN KONEKSI MATEMATIKA DAN MINAT BELAJAR MATEMATIKA SISWA SMP MUHAMMADIYAH KUPANG DENGAN MODEL PMRI - Sopia Maanana; Uke Ralmugiz; Agustin Fatmawati (Program Studi Pendidikan Matematika, Universitas Muhammadiyah Kupang, 2022)
This study aims to find out whether the application of the PMRI learning model can improve the ability of mathematical connections and mathematics learning interest in SMP Muhammadiyah Kupang students. The research used was Classroom Action Research (CAR) with the PMRI learning model. The subjects and objects in this study were 24 students in class VIIA Muhammadiyah SMP Muhammadiyah Kupang. Data collection techniques and instruments used by researchers are the final test questions to find out the ability of mathematical connections and questionnaire sheets to determine student learning interest. The data analysis technique conducted in this study is to draw conclusions from the data obtained, namely the results of the interview, the results of student evaluation and the questionnaire of mathematics learning interest. The results of research conducted in two cycles showed an increase in the ability of students' connections and learning interest through the PMRI approach. Mathematical connection capability test results increased with initial data with an average of 46.17 to 69.62 in cycle 1 then in cycle 2 to 77.29. And mathematics learning interest from the initial condition 41.66% to 70.83% in cycle 1 then in cycle 2 to 87.5%